1973
DOI: 10.1177/030006057300100203
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Trial of Baclofen in Children with Cerebral Palsy

Abstract: A double-blind crossover trial against placebo was conducted to assess the effects of the GAB A derivative, baclofen, on the disabilities due to muscle spasticity in twenty children suffering from cerebral palsy. Baclofen performed very significantly better than placebo in reducing spasticity and significantly better than placebo in allowing both active and passive limb movements to be carried out. Notable improvement was also seen in scissoring. Side-effects were minimal and responded promptly to dose reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
4

Year Published

1983
1983
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 6 publications
1
38
0
4
Order By: Relevance
“…A double-blind crossover trial in 20 children 2-16 years old receiving a dose of 10 -60 mg/day found a reduction in spasticity by means of the AS (p Ͻ 0.001). 7 After 28 days of treatment, 14 patients improved at least 1 level and 5 improved more than 1 level. Only 2 patients improved while taking placebo.…”
Section: E1mentioning
confidence: 93%
See 1 more Smart Citation
“…A double-blind crossover trial in 20 children 2-16 years old receiving a dose of 10 -60 mg/day found a reduction in spasticity by means of the AS (p Ͻ 0.001). 7 After 28 days of treatment, 14 patients improved at least 1 level and 5 improved more than 1 level. Only 2 patients improved while taking placebo.…”
Section: E1mentioning
confidence: 93%
“…6 Alleviation of spasticity may not always be desirable; some patients may experience a decline in function with spasticity reduction. 7 The decision to use antispasticity medications requires careful assessment of the patient's other impairments (e.g., weakness, movement disorders) and proper selection and use of the treatment. Reasons to treat spasticity include reducing pain and muscle spasms, facilitating brace use, improving posture, minimizing contractures and deformity, facilitating mobility and dexterity, and improving patient ease of care as well as hygiene/self-care.…”
mentioning
confidence: 99%
“…23,24 Baclofen and benzodiazepines act centrally on synaptic neurotransmission, and dantrolene directly affects muscle contractility and has proven useful in treating the spasticity of cerebral palsy. 25 Hepatoxicity is a serious issue with long-term use of dantrolene in 1% of cases, and adverse effects include excessive weakness and gastrointestinal distress.…”
Section: Ongoing Care In the Medical Homementioning
confidence: 99%
“…São utilizadas doses progressivas, de até 80-120 mg ao dia, podendo chegar a160 mg ao dia.. Os efeitos colaterais são sonolência, tontura, mal-estar, ataxia, confusão mental, cefaléia, depressão respiratória e cardiovascular e alucinações. 3,15,23 Os benzodiazepínicos atuam nos receptores GABA pré e pós-sinápticos (aumentando a afinidade dos receptores GABA por GABA endógeno), aumentando a inibição sináptica ao nível espinhal e supra-espinhal. Utilizam-se o diazepam e clonazepam.…”
Section: Tratamentounclassified
“…Os efeitos colaterais são muito semelhantes aos do baclofen, principalmente a sedação, sonolência, astenia e agitação paradoxal. 3,15,23 O dantrolene sódico é medicamento de ação periférica, em nível muscular, através do bloqueio da liberação de cálcio no retículo sarcoplasmático, com subseqüente inibição da despolarização. As doses preconizadas estão entre 50 a 800 mg ao dia.…”
Section: Tratamentounclassified